Molecular characterization of Nagaland Long Hair Goat - G, Zaman; N, Nahardeka; A, Aziz; M, Chandra Shekar; K, Sharma; Rakesh, Parikh (International Multidisciplinary Research Journal, 2013)
Nagaland Long hair goat comprises a small population of non-descript indigenous animals. Twenty microsatellite markers on Nagaland Long Hair goat (NLHG) were tested to understand the genetic diversity within the population. All the loci studied were polymorphic in nature. The number of observed alleles (Na) detected ranged from 2 to 8 with an overall mean of 5.0±1.716. A total of 100 alleles were observed across all loci. The effective number of alleles (Ne) ranged from 1.2195 to 5.4340 with a mean of 2.93±1.330. The allele frequency ranged from 0.0312 to 0.9000. Overall mean observed (HO) and expected (He) heterozygosity were 0.56 and 0.48 this population was in Hardy-Weinberg equilibrium at most of the loci studied. The overall mean within-population inbreeding estimate (FIS) was 0.058. The population was stable with respect to size and was non-bottlenecked. The observed normal L – shaped curve indicated no mode shift in the population.